Dissolved iron and iron(II) distributions beneath the pack ice in the East Antarctic (120°E) during the winter/spring transition. (September 2016) - Schallenberg, Christina; van der Merwe, Pier; Chever, Fanny; Cullen, Jay T.; Lannuzel, Delphine; Bowie, Andrew R.
Abstract: Distributions of dissolved iron (dFe) and its reduced form, Fe(II), to a depth of 1000 m were investigated under the seasonal pack ice off East Antarctica during the Sea Ice Physics and Ecosystem experiment (SIPEX-2) sea-ice voyage in September–October 2012. Concentrations of dFe were elevated up to five-fold relative to Southern Ocean background concentrations and were spatially variable. The mean dFe concentration was 0.44±0.4 nM, with a range from 0.09 to 3.05 nM. Profiles of dFe were more variable within and among stations than were macronutrients, suggesting that coupling between these biologically-essential elements was weak at the time of the study. Brine rejection and drainage from sea ice are estimated to be the dominant contributors to elevated dFe concentrations in the mixed layer, but mass budget considerations indicate that estimated dFe fluxes from brine input alone are insufficient to account for all observed dFe. Melting icebergs and shelf sediments are suspected to provide the additional dFe. Fe(II) was mostly below the detection limit but elevated at depth near the continental shelf, implying that benthic processes are a source of reduced Fe in bottom waters. The data indicate that dFe builds up under the seasonal sea-ice cover during winter and that reduction of Fe may be hampered in early spring by several factors such as lack of electron donors, low biological productivity and inadequate light below the sea ice. The accumulated dFe pool in the mixed layer is expected to contribute to the formation of the spring bloom as the ice retreats.